Aplikasi Sistem Pendaftaran Online Pasien Rawat Jalan Berbasis Web Pada Rumah Sakit Umum PKU Muhammadiyah Bantul Yogyakarta - Kusnadi Kusnadi; Nani Purwati; Lina Ayu Safitri (Universitas Muhammadiyah Purworejo, 2019)
PKU Muhammadiyah Bantul general hospital, including hospitals that have used a computerized system in the process of service to patients. One of them in the registration system. Although already using a computerized system, but there are still obstacles in its application, such as the length of the queue which results in delayed service or patient handling. Seeing these conditions, this study aims to design a patient registration system, especially on-site online outpatient services. This research is a qualitative descriptive study, which illustrates how the application of outpatient registration information systems in hospitals. Data collection is done by interview, observation and literature study. From the results of this study, it can be concluded that using the website can simplify the online outpatient registration system.